Wabah malaria di Kulon Progo tahun 1930-an - Shofi Sani; H.Y. Agus Murdiyastomo (Historiography: Journal of Indonesian History and Education, 2023)
This study aims to examine malaria which was endemic in Kulon Progo in the 1930s, including the spread of the outbreaks, causes, and also the countermeasures taken to control it. The research uses historical research methods consisting of heuristics, verification, interpretation, and historiography. The results of this study indicate that in the 1930s, malaria outbreaks infected many people in Kulon Progo, especially in Adikarto Regency. Poor drainage was the main cause that drove malaria to become an epidemic in Kulon Progo. In this case, the malaria outbreak that was spreading in Kulon Progo was handled by bringing the orderlies to give medicine to the sufferers and improving the quality of water drainage.Penelitian ini bertujuan untuk mengkaji tentang malaria yang mewabah di Kulon Progo pada tahun 1930-an, yakni meliputi persebaran, penyebab, dan juga penanggulangan yang dilakukan. Adapun metode penelitian yang digunakan menggunakan metode penelitian sejarah yang terdiri atas heuristik, verifikasi, interpretasi, dan historiografi. Hasil dari penelitian ini menunjukkan bahwa pada tahun 1930-an, wabah malaria banyak menjangkit masyarakat di Kulon Progo terutama di Kabupaten Adikarto. Drainase yang tidak begitu baik menjadi penyebab utama yang mendorong malaria dapat mewabah di Kulon Progo. Wabah malaria yang menjangkit di Kulon Progo ditanggulangi dengan cara mendatangkan para mantri untuk memberikan obat kepada para penderita dan meningkatkan kualitas drainase air.